Conceptual model of information and monitoring systems of the national security - Богданович, Володимир Юрійович; Висідалко, Андрій Леонідович (Ukrainian Information Security Research Journal, 2014)
To improve of the efficiency the functioning of the national security system (NSS) of Ukraine regarding the implementation of its national interests (NI) under the action of various threats, it is necessary to perfect the scientific and methodological apparatus and mechanisms of information and monitoring system of the National Security (IMS NS). At the terms of absence in Ukraine the completed proper scientific developments question of determination of indicators, integral indexes and complex criteria for evaluating of the effectiveness of IMS NS are still relevant. Therefore in the research the conceptual model information and monitoring systems of the national security (IMS NS) is developed, the processes of functioning IMS NS are formalized in the conditions of action of the internal and external threats, the dependence of the efficiency functioning of the IMS NS is shown on the factor of time, the objective function, integral indexes, base indicators and criteria of estimation of functioning IMS NS are defined. The Using of the results of the theoretical researches will allow complex to walk up to development of method for evaluating of the effectiveness of IMS NS.